Heavy-mineral analysis as a tool in tephrochronology, with an example from the La Sal Mountains, Utah, U.S.A. - Kleber, Arno (Geologos, 2013)
An essentially pure tephra layer on a steep slope in the La Sal Mountains, Utah, U.S.A., is correlated with the 1.65 Ma old Guaje Tephra derived from the Jemez Mountains, New Mexico, U.S.A. The heavy-mineral contents and glass shards in sediments beneath the La Sal tephra layer indicate that tephra constituents are contained in deposits considerably older than the pure layer. This suggests that tephra material may become reworked while retaining its pure character, possibly due to laminar transport or to dislocation in a frozen condition. This raises the need to handle tephrochronological findings with great care.